Addressing COVID-19 pandemic implication on mental health in community: Perspective towards important issue behind the crisis - Prabandari, Valentina Lakhsmi (BKM Public Health and Community Medicine, 2021)
Objective: COVID-19 pandemic gives rise to various health problems experienced by everyone in a community, not only physical condition but also psychosocial condition. COVID-19 was stated to be associated with an increased risk of psychiatric disorders. Nevertheless, besides the stigma on COVID-19, COVID-19 survivors may avoid being open and aware of their mental health condition because of public stigma on mental health. This might lead to late management of mental health and psychosocial issues. The purpose of this initiative was to give a view of the management of mental health care and psychosocial support by empowering the role of community and Puskesmas as one of the closest parts of the health system to the community. Content: Mental health has been the concern of health programs done by Puskesmas through promotive, preventive, curative, and rehabilitative efforts. One measure to be done is to perform monitoring of mental health status of COVID-19 survivors using digital health instruments. Mobile phone-based monitoring might allow early detection and treatment toward mental or psychosocial issues experienced by COVID-19 survivors. Promotive and preventive messages can be shown at the end of the questionnaire. Furthermore, there should be a program designed to develop community-based mental health support by implementing DKJPS (Dukungan Kesehatan Jiwa dan Psikososial) through a collaboration of Puskesmas, community health workers, and other public as well as private sectors. This might be achieved by training and mentoring. The last but not least, there is a need to strengthen the capability of Puskesmas in handling mental health and psychosocial issues by sending psychiatrists or psychologists down to Puskesmas. It doesn’t necessarily mean that they have to be there all the time, but improvement of the capacity of health workers in Puskesmas, as well as consultation and mentoring, are all important needs.